Subparalyzing Doses of Rocuronium Reduce Muscular Endurance without Detectable Effect on Single Twitch Height in Awake Subjects. (2nd May 2019) - Gelberg, Jan; Bentzer, Peter; Grubb, David
Abstract : Purpose . To test the hypothesis that a low-dose rocuronium acts mainly by means of reducing muscular endurance rather than by reducing momentary force. Methods . In a randomized placebo-controlled double-blinded study, eight healthy volunteers were studied in two sets of experiments. In the first set, the subjects made a sustained maximum effort with the dominant hand for 80 seconds while squeezing an electronic handgrip dynamometer at three minutes after intravenous administration of placebo, 0.04 or 0.08 mg/kg rocuronium. Handgrip force at initiation of testing (maximum handgrip force) and after 60 seconds was evaluated. In the second set, the ulnar nerve of the subjects was electrically stimulated every tenth second for at least 10 and a maximum of 30 minutes following the administration of placebo and 0.08 mg/kg rocuronium. Single twitch height of the adductor pollicis muscle was recorded. Results . There was no significant difference in the effect on maximum handgrip force at time 0 between the three different doses of rocuronium. As compared with placebo, handgrip force after 0.08 mg/kg rocuronium was reduced to approximately a third at 60 seconds (214 N (120–278) vs. 69 (30–166);p = 0.008 ), whereas only a slight reduction was seen after 0.04 mg/kg (187 (124–256);p = 0.016 ). Based on these results, the sustained handgrip force after 0.2 mg/kg at 60 seconds was calculated to be 1.27% (95% CI [0.40, 4.03]) of the maximum force of placebo. No effect on single twitch height after 0.08 mg/kg rocuronium at four minutes after drug administration could be detected. Conclusions . Subparalyzing doses of rocuronium show a distinct effect on muscular endurance as opposed to momentary force. The findings support the hypothesis that low doses of rocuronium act mainly by reducing muscular endurance, thereby facilitating, for example, tracheal intubation.